"Only if God wants" Michel de Montaigne's religious vision: fideism (2021)
Is skepticism inseparable from religion? Is it, perhaps that the doubt limits the existence of God, to its belief or rejection? Responding to this issue is the intention of the following approach to the fideist vision of Montaigne. To do so and as a first stage, an attempt will be done to the problem of the faith rule that caused such a noise at the time of the Reformation. Secondly the scope of the tradition will be treated as the instance which gives fullness to the unfounded beliefs and that has its own place within the skepticism of the french thinker. Finally, we will analyze the fideist proposal, its narrow bond with nominalism and its relation with skepticism.